Advancements in mammalian display technology for therapeutic antibody development and beyond: current landscape, challenges, and future prospects - Slavny, Peter; Hegde, Manjunath; Doerner, Achim; Parthiban, Kothai; McCafferty, John; Zielonka, Stefan; Hoet, Rene (Frontiers in Immunology, 2024)
The evolving development landscape of biotherapeutics and their growing complexity from simple antibodies into bi-and multi-specific molecules necessitates sophisticated discovery and engineering platforms. This review focuses on mammalian display technology as a potential solution to the pressing challenges in biotherapeutic development. We provide a comparative analysis with established methodologies, highlighting key aspects of mammalian display technology, including genetic engineering, construction of display libraries, and its pivotal role in hit selection and/or developability engineering. The review delves into the mechanisms underpinning developability-driven selection via mammalian display and their broader implications. Applications beyond antibody discovery are also explored, alongside advancements towards function-first screening technologies, precision genome engineering and AI/ML-enhanced libraries, situating them in the context of mammalian display. Overall, the review provides a comprehensive overview of the current mammalian display technology landscape, underscores the expansive potential of the technology for biotherapeutic development, addresses the critical challenges for the full realisation of this potential, and examines advances in related disciplines that might impact the future application of mammalian display technologies.